The Prevalance of Gastrointestinal Tract Protozoa Using Fecal Examination in Local Chicken(Gallus domesticus) Located in Kramat Village, District of Bangkalan, Bangkalan Regency - Talita Yuanda Reksa; Poedji Hastutiek; Hana Eliyani; Kusnoto Kusnoto; Mufasirin Mufasirin (Journal of Parasite Science (JoPS), 2018)
The aim of this research is to identify the prevalence of gastrointestinal track protozoa in local chicken (Gallus domesticus) located in Kramat Village, District of Bangkalan, Bangkalan Regency using fecal examination. The number of sample used were 140 including 70 samples from rice fields location and 70 samples from fisheries location. The result showed that 54 (38.6%) local chickens were infected by species of Eimeria; E. acervulina (2.5%), E. brunetti (22.8%), E. maxima (46.8%), E. mitis (1.3%), E. necatrix (22.8%), E. praecox (2.5%), and E. tenella (1.3%). The result was made of 16 (22.9%) local chickens in rice fields location and 38 (54.3%) local chickens in fisheries location. The infection of Eimeria sp. on male local chickens were 24 (34.3%) while on the female local chickens were 30 (42.9%). Chi Square Test showed that there was a highly significant difference toward the prevalence in rice fields and fishery locations (p<0.01), but there was no significant difference toward the prevalence of male and female local chickens (p>0.05).